Use of the Rochester Epidemiology Project for Clinical Research in Colon and Rectal Surgery - Lightner, Amy L.; Cima, Robert (Clinics in Colon and Rectal Surgery, 2019)
The Rochester Epidemiology Project (REP), a longitudinal population-based database, is the largest epidemiologic database in the world. Originally established at Mayo Clinic in Rochester, Minnesota, the REP has been instrumental in defining the natural history of disease states and the impact of treatment in a well-defined population. In the United States, the REP has made important contributions to the colon and rectal literature, largely because healthcare is fragmented with no unique identifier to longitudinally follow-up with a patient throughout the system over his or her lifespan. Investigation with the REP has provided insight to the economic burden associated with inflammatory bowel disease, the benefit of screening for colorectal cancer, and the natural history of Mekel's and diverticular disease. In addition to practice changing research, the REP can be used as a model for future linkage systems in the United States.
Keywords: Rochester Epidemiology Project; population-based database; inflammatory bowel disease; colon and rectal cancer; diverticulitis